2015
DOI: 10.1007/s11695-015-1703-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit of Gastric Staple Line Reinforcement (SLR) in Gastrointestinal Surgery: a Meta-analysis

Abstract: BackgroundThe objective of this study was to assess whether the use of staple line reinforcement (SLR) reduces staple line complications (SLC). Mechanical staple lines are essential for gastrointestinal surgery such as bariatric surgery. However, SLC, such as bleeding and leakage, still occur. The purposes of this study were to provide quantitative evidence on the relative efficacy of gastric SLR and to compare the rates of effectiveness of three commonly used methods.MethodsA search of the medical literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 46 publications
3
81
0
3
Order By: Relevance
“…According to the 2012 International Sleeve Gastrectomy Expert Panel Consensus Statement, the use of staple line reinforcement, such as a buttress or over-sewing the staple line, is thought to reduce bleeding along the staple line [20][21][22][23] . However, staple line reinforcement has been shown to be associated with an increased risk of leaks in observational studies [21][22][23] .…”
Section: Sub-group and Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 2012 International Sleeve Gastrectomy Expert Panel Consensus Statement, the use of staple line reinforcement, such as a buttress or over-sewing the staple line, is thought to reduce bleeding along the staple line [20][21][22][23] . However, staple line reinforcement has been shown to be associated with an increased risk of leaks in observational studies [21][22][23] .…”
Section: Sub-group and Sensitivity Analysesmentioning
confidence: 99%
“…According to the 2012 International Sleeve Gastrectomy Expert Panel Consensus Statement, the use of staple line reinforcement, such as a buttress or over-sewing the staple line, is thought to reduce bleeding along the staple line [20][21][22][23] . However, staple line reinforcement has been shown to be associated with an increased risk of leaks in observational studies [21][22][23] . Although the Premier Perspective Hospital Database does not contain information to support identification of over-sewing the staple line, buttress materials can be identified from hospital administrative records by searching for billing records of buttress materials.…”
Section: Sub-group and Sensitivity Analysesmentioning
confidence: 99%
“…8,12 Despite the advances in technology of surgical stapling devices, the rates of bleeding and leakage range from 1-5%, and more than 3% of LSG patients require reoperation. 8,10 A large series has demonstrated that the most serious complications included staple line leaks (0-10%), staple line bleeding (0-10%), and surrounding organ injury (0-5%). 13 Many factors were responsible for these complications including local tissue ischemia, increased intra-gastric pressure and undue lateral traction during gastric resection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more extensive data are needed to clearly determine if staple line reinforcement is beneficial or not. 10 The aim of this study is to detect the outcome of staple line reinforcement in LSG done by suture over-sewing technique in comparison to non-reinforcement in prevention of stable line complications as bleeding and leakage.…”
mentioning
confidence: 99%
“…Intra-operative packing to help control bleeding and allow hemostasis. Packing can be done with inserting gauze to help to identify the bleeding source [20,21]. Suction and irrigation can also help us to identify the source of bleeding and allow for the application of a clip, cauterizing the bleeding points, or application of under-running sutures (Figure 2).…”
Section: Managementmentioning
confidence: 99%